2009
DOI: 10.1007/s00415-009-5337-6
|View full text |Cite|
|
Sign up to set email alerts
|

Predictors and prevalence of low bone mineral density in fully ambulatory persons with multiple sclerosis

Abstract: The implications of having multiple sclerosis (MS) for bone health are incompletely understood. The aim of this population-based study is to identify past and current exposures that are associated with bone mass in fully ambulatory persons with MS up to age 50 years and to determine the prevalence of low bone mineral density (BMD) in this group. We measured BMD (hips, lumbar spine, forearms), physical function, BMI, and serum 25(OH) vitamin D in 55 women and 25 men with MS. Patients provided information on dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 36 publications
1
24
1
1
Order By: Relevance
“…There seems to be no correlation between vitamin D levels and BMD in MS, although this may be due to the small numbers of patients included in the published studies and the different countries in which these studies were conducted [8][9][10]53]. One Australian case-control study found a strong negative correlation between the degree of disability, measured by EDSS, and serum 25-OHD levels, which were mathematically adjusted for the season [66].…”
Section: Vitamin Dmentioning
confidence: 98%
“…There seems to be no correlation between vitamin D levels and BMD in MS, although this may be due to the small numbers of patients included in the published studies and the different countries in which these studies were conducted [8][9][10]53]. One Australian case-control study found a strong negative correlation between the degree of disability, measured by EDSS, and serum 25-OHD levels, which were mathematically adjusted for the season [66].…”
Section: Vitamin Dmentioning
confidence: 98%
“…Early findings in breast and prostate cancer, arthritis, stroke, heart transplantation, and weight loss studies require additional research to confirm early findings and to examine physiologic mechanisms of bone preservation given various possible disease and drug interactions with exercise and bone. Moreover, preliminary research with multiple sclerosis patients who are also susceptible to secondary osteoporosis, have preliminary research to suggest that exercise may improve fracture risk through physical fitness and physical activity [145]. However, intervention studies in these populations using bone outcomes are not available.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the early symptoms of MS can be hard to determine but early diagnosis and treatment leads to a better disease course (5). Although there are many risk factors for developing osteoporosis in the general population, the most extensively studied risk factors in MS patients are physical inactivity, treatment with glucocorticoids, and smoking (4,(6)(7)(8).…”
Section: Risk Factors For Osteoporosis In Msmentioning
confidence: 99%